KONSELING SEBAGAI ALAT UNTUK MENEMUKAN TUJUAN HIDUP DAN MEMBANGUN MASA DEPAN YANG CERAH DALAM PERSPEKTIF MANAJEMEN DAKWAH - Novia Rahma Aulia; Ade Titie Solihati; Sukma Bangkit Panji Muslim; Meity Suryandari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Counseling is an important process in helping individuals find life purpose and build a bright future. This study aims to explore the role of counseling in the context of da'wah management to help individuals achieve clearer and more directed life goals. The method used is a literature study by analyzing various literature related to counseling and da'wah management. The results showed that counseling can strengthen individuals' understanding of their life goals and provide effective tools to plan for a better future. These findings support the integration of counseling in da'wah management programs to improve the quality of life and effectiveness of da'wah programs. Keywords: Conseling, Da’wah Management, Life Purpose